Challenging gender equality in South African transformation policies - a case of the White Paper: A programme for the transformation of higher education - Akala, Betty M. (South African Journal of Higher Education, 2018)
Using a post-structural lens, I make arguments against homogenising people’s conditions and circumstances. In particular, I acknowledge that the post-1994 reform agenda intended to streamline the previously fragmented and segregated higher education landscape under the apartheid regime. Black women, who are the main target of this article suffered triple marginalisation ‒ race, social class and sexism. The aim of the article is to show the tensions that exist within the White Paper: A Programme for the Transformation of Higher Education (DoE 1997). The said tensions have stifled the attainment of gender equity and equality; effectively widening the gender fissures in post-1994 South African higher education. I argue that we should not take for granted phrases such as “equal opportunities” and “equal access” in policies. Instead, we should seek their meaning and achievement inter alia in earnest for the targeted group.Therefore, I postulate that gender and gendering is complex and very fragmented. For this reason, formulating transformation interventions on the premise of equality for all does not necessarily guarantee gender equality or gender equity. With this in mind, a “one-size fits all” approach to redressing gender equality is implausible and does not suffice in addressing salient gender injustices. I propose a multifaceted approach, which encompasses a realistic and holistic outlookon the divergent needs of black women in particular and women in general as a possible solution to the current challenges.
Keywords: 1900-1999; 1990-1999; 2000 à aujourd'hui; 2000-2009; 2010-2019; afrique; afrique du sud; approches et analyses; discipline; histoire et politique; patriarcat; post-structuralisme; projet charge mentale; périodes historiques; racisme; ressource en ligne; régions géographiques; science de l'éducation; sexisme; système colonial; systèmes d'oppressions; thématiques; travail; éducation des femmes*

The challenges of women leaders of business organizations in Addis Ababa, Ethiopia, in balancing work-family responsibilities. - Bahiru, Bruktawit; Mengistu, Abeba Beyene (Journal of International Women's Studies, 2018)
Women's leadership significantly contributes to building high-performing organizations. However, challenges with balancing work and family responsibilities are inhibiting them from exerting their fullest potential towards this end. This study aims at investigating the challenges women leaders in Addis Ababa face in balancing the demands of their organizations with that of their families. A sample of eight women leaders of positions from large and middle scale organizations were taken using a purposive sampling technique. In-depth interviews were used to gather information for the study, and a phenomenological qualitative study was applied to analyze the data. The study identified some organizational, societal, and individual factors that challenge women leaders in balancing their work and family responsibilities. Work overload, cultural and social norms, family responsibilities, and upbringing related behaviors of the interviewees themselves were among the major challenges in maintaining their work-family balance. This study contributes insights into work-family balance theory and practice, by presenting women leaders' voices about their work-life challenges as expressed in their own words, from their own testimonies. It indicates that much needs to be done on the part of organizations, society, family, and women themselves for women leaders to have the desired level of work-family balance.
Keywords: 2000 à aujourd'hui; afrique; approches et analyses; conciliation famille-travail; discours dominant; famille; inégalités; projet charge mentale; périodes historiques; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; travail; éthiopie

Jazz, gender, historiography: A case study of the "Golden Age" of jazz in Montreal (1925-1955) - Blais-Tremblay, Vanessa (Université McGill, 2018)
Cette dissertation se penche sur les interactions entre le jazz, l'identité, la nation et la modernité durant le soi-disant âge d'or du jazz à Montréal (1925-1955). À la croisée de la musicologie, des études de la condition féminine (études féministes noires et méthodes de recherche féministes en particulier), des études des médias et des études culturelles, je propose une réécriture critique de l'histoire du jazz montréalais, attentive au rôle que les femmes racisées et ethnicisées ont joué dans le développement de la scène jazz, et plus largement dans la formation des identités, des plaisirs, et des sons de la modernité québécoise. Le statut particulier de Montréal comme ville-spectacle en fait un riche laboratoire pour étudier les relations de collaboration créative entre les artistes (musiciens.ennes, chanteurs.euses, danseurs.euses) actifs sur le circuit du spectacle de variété noir du début du XXe siècle. Cette recherche met également en lumière la relation discursive qu'entretiennent le jazz et le vice dans l'entre-deux-guerres québécois, en particulier quant à l'incarnation sexuée et racisée de la moralité. Finalement, cette dissertation présente la première écoute critique ainsi que les premières notes biographiques détaillées d'artistes féminines de jazz montréalaises telles que les pianistes Vera Guilaroff et Ilene Bourne, des ensembles féminins comme les Sœurs Spencer et le Montreal Melody Girls Orchestra, des danseuses et chanteuses de variété noires telles que Tina Baines Brereton, Bernice Jordan Whims, Mary Brown, Natalie Ramirez, et Marie-Claire Germain, ainsi que l'enseignante de piano Daisy Peterson Sweeney et les enseignantes de danse Ethel Bruneau et Olga Spencer Foderingham.
Keywords: 1900-1999; 1920-1929; 1930-1939; 1940-1949; 1950-1959; DIG; amérique du nord; amériques; approches et analyses; arts; canada; discipline; femmes* artistes; histoire; histoire et politique; historiographie; intersectionnalité; montréal; musique; mémoires/thèses; point de vue situé; périodes historiques; québec; ressource en ligne; régions géographiques; sciences humaines; thématiques; travail

Aux marges de l'emploi: parcours de travailleuses domestiques québécoises, 1950-2000 - Charron, Catherine (Les éditions du remue-ménage, 2018)
Keywords: 1900-1999; 1950-1959; 1960-1969; 1970-1979; 1980-1989; 1990-1999; amérique du nord; amériques; approches et analyses; canada; care; corps; cours; discipline; his4550; histoire; justice sociale; premier cycle; périodes historiques; québec; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; travail; travail domestique

“I can never be too comfortable”: Race, gender, and emotion at the Hospital Bedside - Cottingham, Marci D.; Johnson, Austin H.; Erickson, Rebecca J. (Qualitative Health Research, 2018)
In this article, we examine how race and gender shape nurses’ emotion practice. Based on audio diaries collected from 48 nurses within two Midwestern hospital systems in the United States, we illustrate the disproportionate emotional labor that emerges among women nurses of color in the white institutional space of American health care. In this environment, women of color experience an emotional double shift as a result of negotiating patient, coworker, and supervisor interactions. In confronting racist encounters, nurses of color in our sample experience additional job-related stress, must perform disproportionate amounts of emotional labor, and experience depleted emotional resources that negatively influence patient care. Methodologically, the study extends prior research by using audio diaries collected from a racially diverse sample to capture emotion as a situationally emergent and complex feature of nursing practice. We also extend research on nursing by tracing both the sources and consequences of unequal emotion practices for nurse well-being and patient care.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; infirmières; intersectionnalité; projet charge mentale; périodes historiques; racisme; régions géographiques; santé; sexisme; systèmes d'oppressions; systèmes hospitaliers; thématiques; travail; travail émotionnel; états-unis

Against the odds? Keeping a nontraditional division of domestic work after first parenthood in Spain. - Dominguez-Folgueras, Marta; Jurado-Guerrero, Teresa; Botía-Morillas, Carmen (Journal of Family Issues, 2018)
This article analyzes changes in the division of routine domestic work after first parenthood. We wanted to know whether and how it was possible for couples to resist the trend toward traditionalization that has been shown in the literature. To do so, we analyze semistructured interviews with 27 Spanish couples who were expecting their first child in 2011 and interviewed them again in 2013. The couples were selected from a bigger sample because of their nontraditional practices preparenthood. Our results show that 17 of them were able to maintain a nontraditional division of domestic work, whereas 10 traditionalized. In our analysis, relative resources and time availability did not sufficiently explain the changes in the division of work, but specific characteristics of the division of work before childbirth—men’s active participation, the routinization of tasks, and flexible standards—emerged as key factors to resist the trend toward more traditional arrangements. © 2017, © The Author(s) 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; discipline; division sexuelle du travail; espagne; europe; famille; maternité; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; thématiques; travail; travail domestique

Dancing backwards in high heels: Female professors experience more work demands and special favor requests, particularly from academically entitled students - El-Alayli, Amani; Hansen-Brown, Ashley A.; Ceynar, Michelle (Sex Roles, 2018)
Although the number of U.S. female professors has risen steadily in recent years, female professors are still subject to different student expectations and treatment. Students continue to perceive and expect female professors to be more nurturing than male professors are. We examined whether students may consequently request more special favors from female professors. In a survey of professors (n = 88) across the United States, Study 1 found that female (versus male) professors reported getting more requests for standard work demands, special favors, and friendship behaviors, with the latter two mediating the professor gender effect on professors’ self-reported emotional labor. Study 2 utilized an experimental design using a fictitious female or male professor, with college student participants (n = 121) responding to a scenario in which a special favor request might be made of the professor. The results indicated that academically entitled students (i.e., those who feel deserving of success in college regardless of effort/performance) had stronger expectations that a female (versus male) professor would grant their special favor requests. Those expectations consequently increased students’ likelihood of making the requests and of exhibiting negative emotional and behavioral reactions to having those requests denied. This work highlights the extra burdens felt by female professors. We discuss possible moderators of these effects as well as the importance of developing strategies for preventing them. © 2017, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: amériques; approches et analyses; discipline; femmes professeures; milieux universitaires; projet charge mentale; psychologie; psychologie sociale; rapports sociaux de sexe; régions géographiques; sciences humaines; stéréotypes de genre; thématiques; travail; travail émotionnel; états-unis

Un autre regard 2 : fallait demander - Emma (Massot éditions, 2018)
Un autre regard Trucs en vrac pour voir les choses autrement Jusqu'en 2010, je suis une petite citoyenne modèle. J'étudie, puis je travaille, je soutiens des associations charitables, je vote, et je trie soigneusement mes emballages. Je vois bien que le monde va mal et je pense que c'est à cause des gens gui n'étudient pas, ne travaillent pas, ne soutiennent pas d'associations, ne votent pas, et ne trient pas leurs emballages. À 30 ans, je passe, en partie, du côté de celles et ceux que le système abîme. Je réalise que loin d'avoir contribué à améliorer ma société, j'ai participé à son délitement. Je m'éveille politiquement. Ce monde que je me mets à voir différemment, je veux, le révéler à tout.e.s. Alors en 2016, je commence à dessiner mes pensées et mes découvertes, en expliquant le cheminement gui m'y a amenée. Ce livre est Le fruit d'observations et de réflexions mises en images au fil de l'actualité Une autre façon de voir notre monde pour aboutir, collectivement, à une autre façon de le faire tourner.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; bande-dessinée; charge mentale; charge émotionnelle; corps; maternité; patriarcat; projet charge mentale; périodes historiques; sexisme; systèmes d'oppressions; thématiques; travail; violences

Les solidarités familiales sous l’angle du travail: un siècle au Québec - Kempeneers, Marianne; Van Pevenage, Isabelle; Dandurand, Renée B. (Nouvelles Questions Féministes, 2018)
Les femmes sont le pivot des solidarités familiales, c’est un fait solidement documenté. Malgré cette évidence empirique, les solidarités familiales n’occupent qu’une place fort discrète dans l’univers théorique des rapports sociaux de sexe, contrairement par exemple au travail domestique ou, plus récemment, au travail du care. Les auteures s’interrogent ici sur cet état de fait. Elles proposent ensuite une lecture des solidarités familiales avec, pour ancrage, le paradigme fondateur que constitua la refonte du concept de travail par les courants féministes matérialistes. Adoptant une perspective historique et macrosociologique, cet article est l’occasion de prendre du recul face à un certain nombre de résultats issus d’une vaste enquête que les auteures avaient menée en 2004 sur les transformations des solidarités familiales au Québec au long du XXe siècle. La profondeur historique de cette enquête fait en sorte que ces données, bien que recueillies en 2004, restent pertinentes pour leur propos, à savoir jeter un éclairage sur les logiques reliant les évolutions concomitantes des solidarités familiales, du travail des femmes et des politiques publiques au Québec durant ce siècle crucial de son histoire.
Keywords: 1900-1999; 1960-1969; 1970-1979; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; amérique du nord; amériques; approches et analyses; canada; care; cours; discipline; famille; histoire et politique; hétérosexualité; inégalités; maternité; patriarcat; premier cycle; périodes historiques; québec; régions géographiques; sciences humaines; sexualité; soc2264; sociologie; systèmes d'oppressions; thématiques; travail

Documenting a labor of love: Emotional labor as academic labor - Lawless, Brandi (Review of Communication, 2018)
Les pratiques néolibérales ancrées dans le milieu universitaire ont transformé l’université en une industrie de services. À travers ce prisme, cette revue documente l’exploration actuelle du travail émotionnel dans le milieu universitaire, en particulier dans les études en communication. Bien qu’il existe peu de littérature sur ce sujet, j’explore comment un programme néolibéral crée une attente pour les professeurs de communication d’effectuer un travail émotionnel (et comment cette attente est plus grande par rapport à d’autres domaines), les façons dont le travail émotionnel est vécu différemment par les femmes et comment les études en communication en tant que domaine genré exacerbent les attentes d’effectuer un tel travail. De plus, je souligne l’évolution de la perception du domaine et les mouvements connexes pour élargir le travail émotionnel. Enfin, j’évoque les moyens d’avancer dans un milieu universitaire néolibéral.
Keywords: approches et analyses; communication; discipline; inégalités; politiques néolibérales; projet charge mentale; ressource en ligne; sexisme; systèmes d'oppressions; thématiques; travail; travail émotionnel; universitaires

The Routledge handbook of gender and violence - Lombard, Nancy (Routledge handbooks, 2018)
The Routledge Handbook of Gender and Violence provides both a comprehensive and authoritative state-of-the-art overview of the latest research in the field of gender and violence. Each of the 23 specially commissioned chapters develops and summarises their key issue or debate including rape, stalking, online harassment, domestic abuse, FGM, trafficking and prostitution in relation to gender and violence. They study violence against women, but also look at male victims and perpetrators as well as gay, lesbian and transgender violence. The interdisciplinary nature of the subject area is highlighted, with authors spanning criminology, social policy, sociology, geography, health, media and law, alongside activists and members of statutory and third sector organisations. The diversity of perspectives all highlight that gendered violence is both an age-old and continuing social problem. By drawing together leading scholars this handbook provides an up-to-the-minute snapshot of current scholarship as well as signposting several fruitful avenues for future research. This book is both an invaluable resource for scholars and an indispensable teaching tool for use in the classroom and will be os interest to students, academics, social workers and other professionals working to end gender-based violence.
Keywords: approches et analyses; communication; cours; criminologie; discipline; droit; géographie; justice sociale; outils; ouvrages de références; premier cycle; rapports sociaux de sexe; ressource en ligne; santé; science politique et droit; sciences humaines; sex1911; sexualité; sociologie; sofia; thématiques; travail; violences

S’organiser autrement : la prise de parole et de décision dans les organisations féministes - Meunier, Véronique (Université de Montréal, 2018)
Ce mémoire explore les processus interactionnels et les pratiques décisionnelles au sein des organisations féministes et les manières dont les participantes en font sens. Une revue de la littérature a démontré que les organisations féministes portent une attention particulière à l’inclusion des participantes dans le groupe et tentent souvent d’instaurer des rapports égalitaires entre les membres. L’observation de réunions d’une organisation sélectionnée a permis de décrire les pratiques et les stratégies utilisées par les membres. Il a été observé que plusieurs mécanismes contribuent à la création d’un climat de participation et d’échanges dans le groupe. Six entretiens semi-dirigés ont été réalisés avec des participantes de l’organisation afin de comprendre comment elles-mêmes font sens de leur expérience au sein du groupe. Il a émergé des observations que le souci d’inclusion des participantes se manifeste lors des processus de prise de décision, notamment avec la recherche de consensus. Les résultats suggèrent également que les participantes sont parfois confrontées à des contradictions entre les idéaux féministes et la pratique.
Keywords: 2000 à aujourd'hui; 2010-2019; EDI; communication; discipline; inclusion; mémoires/thèses; organisations féministes; pratiques féministes; périodes historiques; ressource en ligne; thématiques; travail; étude qualitative

Emploi du temps : la charge de travail totale, le travail non rémunéré et les loisirs - Moyser, Melissa; Burlock, Amanda (Statistiques Canada, 2018)
Keywords: amériques; approches et analyses; canada; inégalités; projet charge mentale; régions géographiques; statistiques; systèmes d'oppressions; thématiques; travail; travail domestique; travail invisible

My butch career: A memoir - Newton, Esther (Duke University Press, 2018)
During her difficult childhood, Esther Newton recalls that she “became an anti-girl, a girl refusenik, caught between genders,” and that her “child body was a strong and capable instrument stuffed into the word ‘girl.’” Later, in early adulthood, as she was on her way to becoming a trailblazing figure in gay and lesbian studies, she “had already chosen higher education over the strongest passion in my life, my love for women, because the two seemed incompatible.” In My Butch Career Newton tells the compelling, disarming, and at times sexy story of her struggle to write, teach, and find love, all while coming to terms with her identity during a particularly intense time of homophobic persecution in the twentieth century. Newton recounts a series of traumas and conflicts, from being molested as a child to her failed attempts to live a “normal,” straight life in high school and college. She discusses being denied tenure at Queens College—despite having written the foundational Mother Camp—and nearly again so at SUNY Purchase. With humor and grace, she describes the influence her father Saul's strong masculinity had on her, her introduction to middle-class gay life, and her love affairs—including one with a well-known abstract painter and another with a French academic she met on a spur-of-the-moment trip to Mexico and with whom she traveled throughout France and Switzerland. By age forty, where Newton's narrative ends, she began to achieve personal and scholarly stability in the company of the first politicized generation of out lesbian and gay scholars with whom she helped create gender and sexuality studies. Affecting and immediate, My Butch Career is a story of a gender outlaw in the making, an invaluable account of a beloved and influential figure in LGBT history, and a powerful reminder of just how recently it has been possible to be an openly queer academic.
Keywords: amériques; approches et analyses; autobiographie; butch; histoire et politique; hétérosexisme; identités LGBTQIA2+; queer; ressource en ligne; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; violences; états-unis

Enquête sur le portrait sociodémographique et l’égalité homme-femme chez les créatrices et créateurs d’humour au Québec : sommaire 2018-2 : données sur la perception de l’égalité entre les femmes et les hommes - Paré, Christelle; Brouard, François (Groupe de recherche sur l’industrie de l’humour (GRIH), SCSE/CSES, Sprott Centre for Social Enterprises / Centre Sprott pour les entreprises sociales (SCSE/CSES), Université Carleton, 2018)
Le Groupe de recherche sur l’industrie de l’humour (GRIH), la Coalition des femmes en humour (Coalition FH), avec l’appui de l’Association des professionnels de l’industrie de l’humour et de l’École nationale de l’humour, se sont unis pour un sondage historique pour l’avenir du milieu de l’humour. Afin de bien saisir le portrait réel de la situation, et de transmettre ce portrait aux décideurs de l’industrie et au public, les partenaires s’unissent pour une enquête. En effet, à ce jour, il est impossible de comparer la situation des créateurs en humour avec ceux d’autres disciplines artistiques, telles que la littérature, la danse, le théâtre ou le cinéma. Afin que les institutions culturelles comprennent davantage qui sont nos créateurs, cette enquête vise à obtenir un portrait de la population des artistes de l’humour sur le territoire québécois.
Keywords: 2000 à aujourd'hui; 2010-2019; arts; genre; périodes historiques; québec; ressource en ligne; régions géographiques; thématiques; travail; étude qualitative; étude quantitative

​Les Expertes s'engagent contre la sous-représentation des femmes dans les médias - Pirot, Olivier (lanouvellerepublique.fr, 2018)
Malgré des efforts et des initiatives, les femmes sont encore sous-représentées dans les médias. Notamment quand il s’agit “ d’expertes ”.
Keywords: 2000 à aujourd'hui; approches et analyses; communication; discipline; inégalités; médias; privilèges masculins; projet charge mentale; périodes historiques; sexisme; systèmes d'oppressions; thématiques; travail

Apprendre l'usage du temps dans les familles cadres: Une enquête en immersion. - Ponsin, Annabelle (Enfances, Familles, Generations, 2018)
Cadre de la recherche : Les pratiques de gestion de parents cadres expriment la normativité des rationalités managériales. Celles-ci renvoie à des raisonnements gestionnaires transversales (sphères privées ou publiques, familiales ou professionnelles, de loisirs) qui dessinent des rapports à soi, aux autres, et au monde (Le Texier, 2016). L’articulation des temps quotidiens (Kaufmann, 1992) et des trajectoires de vie (Bessin 2009) permet de saisir les rapports de classe, d’âge et de genre (Le Feuvre, 2006) en jeu dans ces processus. Les normes temporelles y sont « bricolées » et continuellement rejouées (Canguilhem, 1943 ; De Certeau 1994). Objectifs : J’observe la manière dont ces « temporalités managériales » sont modelées, intériorisées et transmises par les membres du couple (dans leurs vies professionnelles, parentales, conjugales), les enfants (dans leur socialisation, leur scolarité, leur mobilité) et les collectifs familiaux (dans leurs modes de gestion quotidienne). Méthodologie : L’approche qualitative s’amorce par une immersion. En tant que baby-sitter, je remplis un triple rôle : fonctionnel (pour coordonner les activités), éducatif (pour socialiser les enfants à l’enchainement de ces activités) et affectif (pour temporiser les cadences de ces rythmes). Cette immersion se complète par un dispositif d’entretiens et de carnets de bord personnalisés. Résultats : Ces foyers sont des interfaces, semi-ouvertes, de flux. La place que j’y prends est charnière pour comprendre le rôle nodal des mères et des normes éducatives dans la production, la diffusion, l’intériorisation et l’invisibilisation des normes temporelles. Conclusion : Les « modalités de construction » de ces temporalités (Elias, 1997) informent des normativités managériales qui se logent dans nos modes d’être et nos co-constructions intimes. Contribution : L’immersion dans ces territoires temporels, que j’apprivoise, est une clef pour saisir ces processus en leur cœur. Par un retour réflexif sur ma pratique itérative, cet article souligne les co-constructions familiales de normes temporelles managériales.
Keywords: 2000 à aujourd'hui; 2010-2019; care; charge mentale; discipline; europe; france; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sociologie; soins aux enfants; thématiques; travail; travail du care

Travail invisible : portraits d'une lutte féministe inachevée - Robert, Camille; Toupin, Louise (Remue-ménage, 2018)
Encore invisible, le travail des femmes? La question peut faire sourciller tant les féministes ont obtenu des gains sur ce front au cours des dernières décennies. Or, si les femmes ont massivement intégré le marché de l'emploi, le travail dit invisible, majoritairement effectué par celles-ci, n'a fait que croître et se complexifier. En plus du strict travail ménager, il se présente sous de multiples visages: la charge mentale de l'organisation familiale, le travail invisible d'intégration des femmes immigrantes, le travail des proches aidantes, celui des aides familiales venues d'ailleurs, des femmes autochtones et racisées, des étudiantes stagiaires, ou encore, des travailleuses du sexe. Comment se décline l'enjeu du travail invisible dans différents milieux, et où en sont les revendications pour faire reconnaître ce travail et le sortir de l'ombre? Rassemblant des militantes féministes et des intellectuelles engagées sur ces questions, cet ouvrage collectif entend remettre le sujet du travail invisible à l'ordre du jour politique tout en proposant des pistes de réflexion et de mobilisation concrètes
Keywords: amériques; approches et analyses; canada; care; cours; fem1300; femmes* autochtones; femmes* immigrantes; inégalités; premier cycle; québec; racisme; régions géographiques; sexisme; systèmes d'oppressions; thématiques; travail; travail domestique; travail du care; travail du sexe

Des luttes intimes, des luttes collectives - Seery, Annabelle (Travail invisible. Portrait d’une lutte féministe inachevée, 2018)
Keywords: 2000 à aujourd'hui; amériques; charge mentale; couple hétérosexuel; famille; inégalités hommes-femmes; maternité; militance; projet charge mentale; périodes historiques; québec; régions géographiques; thématiques; travail

Linking job work hours to women’s physical health: The role of perceived unfairness and household work hours - Thomas, Candice L.; Laguda, Emem; Olufemi-Ayoola, Folasade; Netzley, Stephen; Yu, Jia; Spitzmueller, Christiane (Sex Roles, 2018)
Although the relationship between job work hours and women’s physical health has been examined, limited empirical research examines the family demand conditions that explain this relationship. Given the challenge of integrating work and family demands, we examine the boundary conditions under which job hours relate to women’s physical health by integrating the influences of household work hours, perceived unfairness of division of household labor, and traditional gender ideology. Using a large, multi-national archival dataset, our results show that women working long job hours are more likely to report decreased physical health and that this relationship is moderated by the hours and fairness perceptions of household labor: The lowest physical health was observed at high job hours and high household hours and also when women felt that they did less than their fair share of household labor. However, looking at the slopes of these relationships, the negative relationship between job hours and physical health was stronger when women worked lower household hours or felt that they contributed less than their fair share of household labor—suggesting that maintaining a contribution to household labor might be important for working women. Furthermore, these results suggest that policy and organizational interventions aimed at supporting women’s physical health could take their household labor contributions and fairness perceptions into account when assessing the negative impact of high job work hours. © 2018, Springer Science+Business Media, LLC, part of Springer Nature.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; conciliation famille-travail; culpabilité; discipline; division sexuelle du travail; famille; projet charge mentale; psychologie; psychologie sociale; périodes historiques; rapports sociaux de sexe; sciences humaines; thématiques; travail; travail domestique

Les cheffes d’entreprise et jeunes entrepreneures de Lomé (Togo) : des « superwomen » de la double journée de travail professionnel et domestique ? - Vampo, Charlotte (Enfances, Familles, Generations, 2018)
Cadre de la recherche : Le Togo, pays à forte tradition commerciale, présente un taux élevé d’activité des femmes. Celles-ci sont encouragées à entreprendre et disposent librement de leurs revenus. Parallèlement, elles ont la charge quasi intégrale du travail domestique. Si la plupart d’entre elles sont cantonnées aux activités informelles, certaines cheffes d’entreprise ont réussi à se faire une place dans la capitale dans des secteurs émergents de l’économie formelle. L’enquête porte sur ces archétypes de l’émancipation féminine par le travail, qui ont fait des études supérieures et qui sont dans des associations qui promeuvent l’entrepreneuriat des femmes et leur empowerment. Objectifs : Cet article explore la manière dont elles adhèrent à la division sexuelle du travail (DST) traditionnelle. Il questionne les ressources dont elles disposent pour gérer leur quotidien entre contraintes familiales et obligations professionnelles dans le but de discuter les reconfigurations dans les rôles genrés. Méthodologie : Pour ce faire, la réflexion s’appuie sur des terrains ethnographiques réalisés à Lomé au cours des cinq dernières années. Une micro-analyse des rapports de genre est privilégiée dans le souci d’appréhender les itinéraires de réussite des entrepreneures dans une approche relationnelle. Le matériel empirique se compose d’entretiens, d’observations en entreprises et en dehors de celles-ci, de discussions informelles et d’un questionnaire sur la répartition des dépenses et des tâches au quotidien. Résultats : Les résultats indiquent que la conciliation travail professionnel-travail domestique est considérée comme un devoir de femme mariée. La principale ressource dont disposent ces femmes pour s’organiser est le transfert des charges domestiques sur d’autres femmes autant au domicile que dans l’entreprise. Conclusions : L’adhésion à la DST est déterminée par la place occupée par le mariage dans la réussite et par des enjeux de reconnaissance sociale associés au rôle reproducteur des femmes. Les cheffes d’entreprise de Lomé ne pourraient pas être les superwomen qu’elles essayent d’être sans le recours à d’autres femmes. Contribution : L’accès des femmes à des postes à fortes responsabilités ne modifie pas complètement les rôles de genre si l’on se penche spécifiquement sur la division sexuelle du travail. La reconfiguration des rapports de genre est partiellement dépendante de l’empowerment économique des femmes. Toutefois, la négociation sociale du statut de cheffe d’entreprise se fait dans la transgression des normes de genre mais surtout dans la perpétuation d’un ordre inégalitaire de genre qui accompagne paradoxalement les changements. Cet article nous invite à reconsidérer l’empowerment comme un processus socio-politique à la fois individuel et collectif.
Keywords: afrique; anthropologie; approches et analyses; conciliation famille-travail; discipline; division sexuelle du travail; droits des femmes*; famille; femmes entrepeneures; histoire et politique; projet charge mentale; rapports sociaux de sexe; régions géographiques; sciences humaines; thématiques; togo; travail

Byproductive labor: A feminist theory of affective labor beyond the productive-reproductive distinction - Whitney, Shiloh (Philosophy and Social Criticism, 2018)
My aim in this paper is to introduce a theory of affective labor as byproductive, a concept I develop through analysis of the phenomenology of various affective labor practices in dialog with feminist scholarship, both on gendered and racialized labor, and on affect and emotion. I motivate my theory in the context of literature on affective and emotional labor in philosophy and the social sciences, engaging the post-Marxist literature on affective and immaterial labor and emphasizing feminist critiques. I argue that affective labor is not only the work of producing affects for others to consume or the reproductive work that rejuvenates and sustains labor power and social life, but also the work of metabolizing waste affects and affective byproducts. Thus, byproductive labor is a neologism I develop to bring into view an affective economy and indeed a political economy of affects to the side of the distinction between productive and reproductive labor in its paid and unpaid variants. I make three central claims: (1) affective labor invariably creates byproducts in the embodied subjectivity of the worker; (2) the unique kind of affective expenditure I call “byproductive” (metabolizing affective surplus, containing affective waste, and producing depleted affective agency) is a defining feature of affective labor not circumscribed by the productive-reproductive distinction; and (3) the marginalized forms of subjectivity and depleted agency constituted through the intersections of this labor with hierarchies of gender, race, and migrant status or global class are themselves byproducts of affective labor. Thus, theorizing affective labor as byproductive captures the uniqueness of affective labor and the forms of exploitation unique to it, but also explains the interaction of affective labor with forms of power that operate through subjection and marginalization. © The Author(s) 2018.
Keywords: amériques; discipline; histoire et politique; philosophie; projet charge mentale; régions géographiques; sciences humaines; thématiques; travail; travail affectif; travail émotionnel; états-unis

The gendered discourse of work-family balance in the oil and gas industry - Williams, Christine L. (Social Currents, 2018)
U.S. corporations have been slow to adopt family-friendly workplace accommodations, despite decades of research demonstrating their value. Some hope that the millennial generation will spur corporate change because, compared with older generations of workers, young people purportedly strive for more balanced lifestyles and gender equality in their relationships. This study examines the experiences of early career scientists and engineers employed by a major oil and gas corporation that has not implemented family-friendly accommodations, asking whether these highly trained workers seek work-family balance and whether they parlay these desires into requests for accommodation from their employer. Interviews reveal a gendered discourse of work-family balance at this firm: mothers and prospective mothers describe intense work-family conflict, but they blame themselves and not their employer. A number of men, in contrast, express satisfaction with their work-family balance, yet their narratives reveal that their achievement of balance depends on a traditional gender division of labor in the home. Some men and women seek alternative forms of balance that do not involve family; if thwarted from pursuing this goal, they are inclined to exit the company. These discourses of balance reflect neoliberal assumptions, reproduce gender inequality, and suggest the need for an alternative to the voluntary approach to promoting work-family policies. © 2017, © The Southern Sociological Society 2017.
Keywords: 2000 à aujourd'hui; 2010-2019; amériques; approches et analyses; capitalisme; conciliation famille-travail; discipline; famille; industrie pétrolière; politiques néolibérales; projet charge mentale; périodes historiques; régions géographiques; sciences humaines; sexisme; sociologie; systèmes d'oppressions; thématiques; travail; états-unis

Prendre en compte les femmes à bas salaires et racisées - Yerochewski, Carole (Nouveaux Cahiers du socialisme, 2018)
Keywords: amériques; approches et analyses; care; cours; discipline; fem1300; inégalités; mouvement syndical; mouvements des femmes*; premier cycle; québec; racisme; rapports sociaux de sexe; ressource en ligne; régions géographiques; sciences humaines; sociologie; systèmes d'oppressions; thématiques; travail

Accidental teachers: The journeys of six japanese women from the corporate workplace into english language teaching - Yoshihara, Reiko (Journal of Language, Identity, and Education, 2018)
This study explores the processual identity formation of six Japanese women who gave up a job, turned to higher education, and became university EFL teachers in Japan. My research questions include: (1) How did they change their careers and become university EFL teachers? (2) Since they entered the university EFL teaching profession, how have they felt about their own gender? and (3) How did their working experience influence their EFL teaching? Drawing on a poststructural feminist theory of identity, I examine their nonlinear, changing and contested teacher identities in social, economic and political contexts. Their stories help us understand the complex relations between individuals and the gendered social world and hidden issues involving self-conflict, a sense of unfairness, the burden of gender-differentiated expectation, and emotional strain. I also draw attention to the use of their former identities as a component of their pedagogy, which leads to feminist teaching.
Keywords: 2000 à aujourd'hui; 2010-2019; approches et analyses; asie; conciliation famille-travail; famille; femmes* universitaires; japon; post-structuralisme; postmodernisme; projet charge mentale; périodes historiques; régions géographiques; thématiques; travail